Comparison of Microstructure and Mechanical Properties of A356/SiC Metal Matrix Composites Produced by Two Different Melting Routes. (20th October 2014) - Dwivedi, Shashi Prakash; Sharma, Satpal; Mishra, Raghvendra Kumar
Abstract : A356/SiC metal matrix composites with different weight percent of SiC particles were fabricated by two different techniques such as mechanical stir casting and electromagnetic stir casting. The results of macrostructure, microstructure, and XRD study revealed uniform distribution, grain refinement, and low porosity in electromagnetic stir casing samples. The mechanical results showed that the addition of SiC particles led to the improvement in tensile strength, hardness, toughness, and fatigue life. It indicates that type of fabrication process and percentage of reinforcement are the effective factors influencing the mechanical properties. It is observed that when percentage of reinforcement increases in electromagnetic stir casting, best mechanical properties are obtained.